Quantifying the triboelectric series - Haiyang Zou (Nature Portfolio, 2019)
Triboelectric charging is a well-known phenomenon, but triboelectric polarization has only been ranked qualitatively. Here the authors develop a quantified triboelectric series for a wide range of polymers by measuring triboelectric charge density with respect to a liquid metal at well-defined conditions.